An atypical Toxoplasma gondii genotype in a rural Brazilian dog co-infected with Leishmania (Viannia) braziliensis - Silva, Rodrigo Costa da; Caffarol, Karen [UNESP]; Paula, Carolina Lechinski [UNESP]; Risseti, Rafaela Mastrangelo [UNESP]; Langoni, Helio [UNESP]; Megid, Jane [UNESP]; Melanchauski, Mariana Serrano [UNESP]; Souza, Katiane Lohn [UNESP]; Takahira, Regina Kiomi [UNESP]; Vasconcelos Machado, Vania Maria de [UNESP] (Soc Brasileira Medicina Tropical, 2015)
Toxoplasmosis and leishmaniasis are two worldwide zoonoses caused by the protozoan parasites Toxoplasma gondii and Leishmania spp., respectively. This report describes the clinical and laboratorial findings of a co-infection with both parasites in a 4-year-old female dog suspected of ehrlichiosis that presented anemia, thrombocytopenia, hypoalbuminemia, hyperglobulinemia, tachyzoite-like structures to the lung imprints, and polymerase chain reaction (PCR) results positive for T. gondii (kidney, lung, and liver) and Leishmania spp. Co-infection with Toxoplasma gondii and Leishmania braziliensis was confirmed by sequencing; restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR) confirmed an atypical T. gondii genotype circulating in dogs that has been reported to cause human congenital toxoplasmosis.
Keywords: Immunosuppression; American visceral leishmaniasis; Toxoplasmosis